2017
DOI: 10.1590/1806-9061-2016-0268
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility and Biofilm Production by Salmonella sp. Strains Isolated from Frozen Poultry Carcasses

Abstract: The objectives of this study were to evaluate the antimicrobial resistance and the biofilm-producing ability of Salmonella sp. strains isolated from frozen poultry carcasses. Antimicrobial susceptibility was tested by the disk-diffusion method. Biofilm-producing ability was determined in 96-well polystyrene microplates stained with crystal violet at 1%. Out of the 22 strains tested, all were multiresistant, that is, resistant to more than three antimicrobial classes, and 72.7% were able to form biofilms. The h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
0
11
1
4
Order By: Relevance
“…In line with our findings, a study conducted by Sereno et al, re-ported that 72.7% of all the isolates could form biofilms, although 13.6%, 59.1%, and 34% were moderate, weak, and strong biofilm producers, respectively. Nonetheless, 27.3% did not form biofilms (15) and inconsistent with the current study, they found no strong biofilm producers. Furthermore, there was a statistically significant correlation between strong biofilm formation and resistance to colistin, ceftazidime, penicillin, gentamicin, chloramphenicol, trimethoprim, and trimethoprim-sulfamethoxazole.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…In line with our findings, a study conducted by Sereno et al, re-ported that 72.7% of all the isolates could form biofilms, although 13.6%, 59.1%, and 34% were moderate, weak, and strong biofilm producers, respectively. Nonetheless, 27.3% did not form biofilms (15) and inconsistent with the current study, they found no strong biofilm producers. Furthermore, there was a statistically significant correlation between strong biofilm formation and resistance to colistin, ceftazidime, penicillin, gentamicin, chloramphenicol, trimethoprim, and trimethoprim-sulfamethoxazole.…”
Section: Discussioncontrasting
confidence: 96%
“…Biofilm formation is one of the characteristics of these microorganism that intensifies the antibiotic resistance dilemma (15). Nowadays, the biofilm formation on equipment and tools is considered as a source of pathogenic bacteria that increases the risk of food product contamination in food processing systems (16).…”
mentioning
confidence: 99%
“…When samples of inoculated raw chicken breast meat were marinated for 8 h in lemon juice alone, reduction in the initial viable count was only 1.12 Log CFU/sample (Figure 2A) which was lower than that observed for planktonic cells exposed to lemon juice for 15 min (Figure 1A). These results are not surprising considering the fact that bacteria attached to surfaces are more tolerant to antimicrobial agents compared to planktonic bacteria (45). For example, Salmonella cells attached to surfaces exhibited far more resistance than planktonic cells to disinfectants used during poultry processing (46).…”
Section: Gc-ms Analysis Of Thyme Oilmentioning
confidence: 87%
“…has great adapting ability to adverse conditions than other pathogenic bacteria due to developing biofilms. Biofilm formation is controlled by both genetic factors and environmental signals (Davey et al, 2003;Sereno et al, 2017).…”
Section: Introductionmentioning
confidence: 99%